Human nature and the evolution of society - Sanderson, Stephen K. (Boulder, Colorado : Westview Press, 2014)
" If evolution has changed humans physically, has it also affected human behavior? Drawing on evolutionary psychology, sociobiology, and human behavioral ecology, Human Nature and the Evolution of Society explores the evolutionary dynamics underlying social life. In this introduction to human behavior and the organization of social life, Stephen K. Sanderson discusses traditional subjects like mating behavior, kinship, parenthood, status-seeking, and violence, as well as important topics seldom included in books of this type, especially gender, economies, politics, foodways, race and ethnicity, and the arts. Examples and research on a wide range of human societies, both industrial and nonindustrial, are integrated throughout. With chapter summaries of key points, thoughtful discussion questions, and important terms defined within the text, the result is a broad-ranging and comprehensive consideration of human society, thoroughly grounded in an evolutionary perspective"--
Preface -- Notes on dating -- Theoretical foundations -- Beginnings -- Getting a living -- Foodways -- Finding mates -- Family and marriage -- Parenthood -- Gender -- Status and wealth -- Power and politics -- Violence -- Race and ethnicity -- Religion -- Arts -- Epilogue : Evolution and existence.
Sisältää bibliografisia viitteitä (sivut 387-426) ja hakemiston.
Julkaistu myös verkkoaineistona.
Keywords: Human behavior; Human evolution; Social evolution; evoluutio; evoluutioteoria; kulttuuriantropologia; kulttuurievoluutio; käyttäytyminen; sosiaalinen käyttäytyminen; evolution; evolutionsteori; kulturantropologi; kulturell evolution; beteende; socialt beteende